1999
DOI: 10.1590/s0037-86821999000300010
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokines in chronic Chagas' disease

Abstract: We studied the serum levels of IL-2, IFN-gamma and TNF in different clinical forms of Chagas' disease and in patients clinically compensated and decompensated. Cytokines measured in 91 patients with the chronic form of the disease did not differ from those of 13 normal individuals, suggesting the absence of activation of the TH1 pattern of lymphocyte response. There were no statistical differences among the 17 patients in the indeterminate form of the disease, the patients presenting either early (n = 4) or we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(7 reference statements)
4
7
1
Order By: Relevance
“…Our results contradict a recent report that did not find detectable levels of TNF-α in serum samples of 91 Chagas disease patients (Ward et al 1999). This is most likely due to the high detection limit of the TNF-α detection kit used by the authors of the previous study (10 pg/ ml) compared to the 0.5 pg/ml quantification level in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results contradict a recent report that did not find detectable levels of TNF-α in serum samples of 91 Chagas disease patients (Ward et al 1999). This is most likely due to the high detection limit of the TNF-α detection kit used by the authors of the previous study (10 pg/ ml) compared to the 0.5 pg/ml quantification level in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…This study showed that serum cytokine levels in patients with the CARD chronic form of the disease did not differ from those of IND patients. Thus, the present results are in agreement with the finding of Ward et al (1999) that similar levels of IFN-γ and TNF-α can be found in the sera of chronic chagasic patients (both IND and CARD form) and NI patients. Interestingly, although these authors used different collection procedures than those used by our group, similar results were obtained.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, no difference was observed in cytokine levels in the sera of chagasic patients with different clinical outcomes. IL-2, IFN-γ, and TNF-α production were similar in all groups of chagasic patients with different forms of the disease (Ward et al 1999). These results were confirmed by other studies, which also showed that, although the levels of TNF-α and NO were higher in sera from chagasic patients, compared to non-chagasic individuals, no difference was observed between asymptomatic and symptomatic chagasic patients (Perez-Fuentes et al 2008).…”
supporting
confidence: 82%
“…In agreement with the results of the present study, Ward et al (22) did not found differences in the levels of IL-2, gamma interferon, and TNF in the sera of children with indeterminate and chronic forms of Chagas disease. On the other hand, Samudio et al (20) have reported the analysis of cytokine profiles in children with Chagas' disease by studying the mRNA by reverse transcription-PCR, and these authors found that the expression of mRNA for gamma interferon, IL-2, IL-4, and IL-10 was elevated in both parasitemic and nonparasitemic children.…”
Section: Discussionsupporting
confidence: 94%